Education in Global Health: Experience in Health-Promoting Schools Provides Trainees with Defined Core Competencies. (13th March 2012) - Moodley, Shreya; Kasangaki, Arabat; Macnab, Andrew J.
Abstract : Introduction . Medical education has defined essential "universal" core competencies. The value of global health education gained through participation in a health-promoting school project was assessed using Canada's CanMEDS roles and competencies. Methods . The project involved health care trainees in delivery of "Brighter Smiles, " a global health education program addressing children's oral health in Canada and Uganda based on the WHO health-promoting (HP) school model. Multidisciplinary teams first visit a Canadian First Nations community for an introduction to HP schooling, team building, and experience working in different cultural environments and then have 4–6 weeks of global health project delivery in rural HP schools in Uganda in partnership with local College of Health Sciences trainees/faculty. Learning opportunities afforded were evaluated by conventional questionnaire and pilot categorization against the 7 CanMEDS roles (divided into 126 core competencies). Results . All collaborator and health Advocate competencies and 16/17 of the communicator roles were addressed. Overall, project experience included 88 (70%) of the 126 competencies. Conclusions . This pilot suggests CanMEDS criteria can be used to effectively evaluate trainee participation in HP school program delivery, allowing the comprehensive educational opportunities to acquire global health knowledge and skills reported by conventional evaluation to be formally categorized against defined educational roles and competencies.